The Inevitability of Playing Politics as Chair: Advantages and Pitfalls - Domenick J Pinto (Academic Chairpersons Conference Proceedings, 2016)
Politics is a term often frowned upon as it pertains to the role of an academic leader. However as chair for almost 29 years it has become an essential yet sometimes unwanted aspect of the daily rigors of the position. This session explores the advantages and pitfalls of “playing politics” as a department chair.
Keywords: politics; leadership; administration; governance; faculty